2016
DOI: 10.1128/jvi.02833-15
|View full text |Cite
|
Sign up to set email alerts
|

Cucumber Necrosis Virus Recruits Cellular Heat Shock Protein 70 Homologs at Several Stages of Infection

Abstract: RNA viruses often depend on host factors for multiplication inside cells due to the constraints of their small genome size and limited coding capacity. One such factor that has been exploited by several plant and animal viruses is heat shock protein 70 (HSP70) family homologs which have been shown to play roles for different viruses in viral RNA replication, viral assembly, disassembly, and cell-to-cell movement. Using next generation sequence analysis, we reveal that several isoforms of Hsp70 and Hsc70 transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 98 publications
3
37
0
Order By: Relevance
“…We wished to determine whether Nicotiana benthamiana HSP70 family homologs play a role in the disassembly of the plant virus Cucumber necrosis virus (CNV). This would extend our previous observation that HSP70 homologs play multiple roles in the CNV multiplication cycle (27).…”
supporting
confidence: 62%
See 2 more Smart Citations
“…We wished to determine whether Nicotiana benthamiana HSP70 family homologs play a role in the disassembly of the plant virus Cucumber necrosis virus (CNV). This would extend our previous observation that HSP70 homologs play multiple roles in the CNV multiplication cycle (27).…”
supporting
confidence: 62%
“…We have previously found that HSP70 homologs play multiple roles in the CNV infection cycle and that Hsc70-2 coimmunoprecipitates with CNV CP (27). This prompted us to determine whether Hsc70-2 is present in CNV particle preparations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aranda et al (1996) also observed during infection with Pea seed-borne mosaic virus that one HSP70 family member, PsHCP71.2, was induced while another, PsHSC71.0, was marginally reduced in transcript level in the tissue where virus was replicating. In N. benthamiana, challenge with five RNA viruses showed significant increases in the expression of multiple HSP70 genes, many encoding proteins that resided in the cytoplasm (Chen et al, 2008;Alam and Rochon, 2015). HSP70 family members also were induced by multiple viruses in Arabidopsis (Whitham et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding HSP70 expression and its effect on virus accumulation or plant phenotype, when one of the HSP70 family members, NbHSP70c-1, was overexpressed, the accumulation of Tobacco mosaic virus was increased (Chen et al, 2008). In Chenopodium quinoa plants heat shocked to induce HSP70 expression and then challenged with CNV, viral genomic RNA accumulation increased (Alam and Rochon, 2015). Silencing the expression of cytosolic Nicotiana HSP70 family members in N. benthamiana using the TRV-or PVXbased VIGS vectors resulted in dwarfed and crinkled leaves or white spots near major veins in developing leaves (Chen et al, 2008;Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%